2017
DOI: 10.4194/1303-2712-v17_6_37
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, microplastic pollution for the first time is reported in the sea surface and water column in Sinop Sarıkum Lagoon coast of the southern Black Sea. Distribution, density and type of microplastics were investigated in the study area where is one of the significant wetlands of the Black Sea. Study was carried out between 2015 and 2016 as seasonally and two types of net for sea surface and water column were used for three different depths. Results showed that microparticle density was 2.6672.325 pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The presence of heavy metals in water, sediment and biota depends on also many environmental factors like influence of industry and other forms of pollution. Although there is no industrial activity in Sarikum Lake, the surplus of coastal litter in the region and microlitter in the water of Sarikum are remarkable (Öztekin and Bat, 2017). The Hg levels are detected low concentrations in all investigated species.…”
Section: Discussionmentioning
confidence: 85%
“…The presence of heavy metals in water, sediment and biota depends on also many environmental factors like influence of industry and other forms of pollution. Although there is no industrial activity in Sarikum Lake, the surplus of coastal litter in the region and microlitter in the water of Sarikum are remarkable (Öztekin and Bat, 2017). The Hg levels are detected low concentrations in all investigated species.…”
Section: Discussionmentioning
confidence: 85%
“…Notwithstanding several studies have demonstrated that low-density microplastics are mainly found in the sea-surface microlayer [82,147], their position in the water column can differ such as in estuarine habitats and they can sink if marine organisms stick to them [16,82,92,148]. For instance, on average of 0.68 particles/m 3 at the ocean surface compared to 0.02 particles/m 3 in the bottom was detected by Kooi [138], while Oztekin [149] discovered a microparticle density of 2.7 particles/m 3 for sea surface and 24 particles/m 3 for the water column. Moreover, microplastics can be redistributed throughout the water column after a storm that can re-suspend litter on the seabed [150].…”
Section: Occurrence and Abundance Of Microplastics In Watermentioning
confidence: 99%
“…The Black Sea, which is surrounded by six countries, is at an increased risk due to the significant discharge of rivers into this semi-enclosed basin. This amplifies the threat of marine litter and plastic pollution, as indicated by various studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%